Predicting Participation and Production Outcomes Through a Two-Dimensional Model of Organizational Commitment - Mayer, Roger C.; Schoorman, F. David (Academy of Management Journal, 1992)
In this study, we tested a two-dimensional model of organizational commitment and theoretically relevant outcomes based on the motivational distinction proposed by March and Simon (1958) between employees' decisions to participate and to produce. We conducted a longitudinal field study involving 288 employees of a financial services organization. Confirmatory factor analyses support the proposed distinction. Commitment leading to participation was called ?continuance commitment?, and that leading to production, ?value commitment.? Analyses of correlations and partial correlations show that turnover is more strongly related to continuance than to value commitment and that performance is more strongly related to value commitment.